(untitled) (Jurnal Bahasa, 2023)
Banjarese is a type of language that forms new words through affixation. There are various types of affixes, some of which are capable of forming allomorphs or variations of morphological form. The paN- affixes are examples that exhibit this phenomenon through nasal segment changes. The purpose of this study is to describe this assimilation process. One set of Banjarese base words was developed from the dictionary. The respondents of the study were asked to pronounce each base word as well as their derived words with the paN- affix. The results found that the change in nasal segment is caused by a process called homorganic nasal assimilation. Through Optimality Theory analysis, it was found that nasal assimilation occurs in order to comply with constraints that exist within this language. This includes the first constraint that prevents the clustering of heterorganic segments from being present in derivative form, which is AGREE (PLACE). In order to comply with the constraint, the nasal segment will have to share the place of articulation with the segment that comes after it. Besides that, there is another constraint that also prevents the nasal segments from losing their nasal feature, which is IDENT-I→O (nasal). In order to comply with this, the coda position of the affix should be filled with the nasal segment in its derived form. This study is expected to add value to previous studies as well as become a pioneer for upcoming studies. Keywords: Banjarese, allomorphs, nasal change, homorganic nasal assimilation, Optimality Theory, constraints Full text: PDF